1930
DOI: 10.1084/jem.51.5.675
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the Phagocytosis of the Pneumococcus by Human Whole Blood

Abstract: 1. The phagocytic titre of whole human blood against the three types of pneumococcus was determined in a number of individuals. The titre varied over a considerable range in different subjects. 2. Contrary to expectation, the titre in early cases of untreated pneumonia was quite high against the infecting organism, pointing to a local rather than a general lowering of resistance in infection with this organism. 3. Sia's work was confirmed, that the specific carbohydrate has a specific anti-phagocytic action on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

1931
1931
1976
1976

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…The streptococcidal action was studied in the whole defibrinated blood by the method of Todd, as employed by Ward (8) and Finland and Sutliff (9) in studying the pneumococcus. Different dilutions of an 18-hour broth culture of the hemolytic streptococcus were added to 0.5 cc.…”
Section: Methods Of Studymentioning
confidence: 99%
“…The streptococcidal action was studied in the whole defibrinated blood by the method of Todd, as employed by Ward (8) and Finland and Sutliff (9) in studying the pneumococcus. Different dilutions of an 18-hour broth culture of the hemolytic streptococcus were added to 0.5 cc.…”
Section: Methods Of Studymentioning
confidence: 99%
“…The antibody response of human beings to Type III pneumococcal pneumonia (3) or to immunization with the specific carbohydrate of this type (4) is quite similar to that of other common pneumococcal types (3,4). The blood of many normal adults and children has bactericidal properties against the Type III pneumococcus (5). This bactericidal power is inhibited by the type-specific capsular polysaccharide and is enhanced by specific antiserum (5a, 6).…”
mentioning
confidence: 99%
“…Earlier studies with pneumococci have indicated that the pneumococcidal power of opsoninleukocyte mixtures and of defibrinated blood is inhibited by the type-specific cap-. sular polysaccharide but not by the heterologous capsular polysaccharides [30][31][32]. It has also been shown that the injection of type 2 capsular polysaccharide into mice increases the infectivity of attenuated type 2 pneumococci and this effect is type-specific [8].…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli with sufficient K antigen to resist killing by complement has been found resistant to phagocytosis [9]. Furthermore, it has been shown that the capsular polysaccharides of pneumococci need not be present around the cell in the form of a capsule to be able to inhibit phagocytosis, but they retain this activity in solution [8,30,31]. In general, the capsule can be regarded as one of the important virulence factors of microorganisms, although bacterial strains possessing well developed capsules are not always virulent for animals.…”
mentioning
confidence: 99%